2020
DOI: 10.1177/2158244020975027
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Diachronic Change in the Use of English Relative Clauses: A Corpus-Based Study and Its Implication for Pedagogy

Abstract: This corpus-based diachronic study aims to investigate the change in the use of English relative clauses over a 45-year time span. It does not only focus on change over time but also change between two varieties of English (British and American). The data were taken from the Brown family of corpora. Each corpus in the Brown family corpora consists of 500 texts of approximately 2,000 words of written published standard English. The finding indicates that the overall trend of the use of relative clauses in writt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…However, Corpus linguistics technologies provide free access to authentic materials that can be adapted according to the need of specific language students, as illustrated in previous sections. The results of this study are in line with the findings of other researchers (e.g., Fajri & Okwar, 2020;Motschenbacher, 2020). Corpus linguistics techniques are useful to highlighted the frequent language structures in any specific discipline.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Corpus linguistics technologies provide free access to authentic materials that can be adapted according to the need of specific language students, as illustrated in previous sections. The results of this study are in line with the findings of other researchers (e.g., Fajri & Okwar, 2020;Motschenbacher, 2020). Corpus linguistics techniques are useful to highlighted the frequent language structures in any specific discipline.…”
Section: Discussionsupporting
confidence: 91%
“…First, the corpus shows the most frequent grammar rules among different registers. For example, Fajri and Okwar (2020) found that the frequency of the relative 'which' has declined in English writing, but the relative pronoun 'that' has noticeably increased. Also, Motschenbacher (2020) found that corpus is a powerful tool to verify the linguistic characteristics of names as they surface in actual language use, especially at the semantic and grammatical levels.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, this was the relative pronoun that , whereas in Kim et al, which also used subject-relative-clause islands, the relative pronoun was who. Analysis of written English corpora shows that that is increasingly more frequent as a relative clause marker than who (Fajri & Okwar, 2020), which could mean the island structure was easier to identify in our sentences than in Kim et al’s, though further research is needed to test this suggestion. Alternatively, the grammar of the L1 may make a difference.…”
Section: Discussionmentioning
confidence: 80%
“…On the one hand, current research on compressed and implicit syntactic features has focused more on L1 English research writers (e.g., Al Fajri & Okwar, 2020;Biber, Gray et al, 2016;Cho & Lee, 2016;Gray, 2015;Hyland & Jiang, 2017;Kim & Crosthwaite, 2019;Lu et al, 2020). On the other hand, a scarcity of studies concentrating on L2 English research writers exists (e.g., Ruan, 2018;Wu et al, 2020;Yin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%